2010
DOI: 10.1007/s10157-010-0345-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical remission of Henoch–Schönlein purpura nephritis after a monotherapeutic tonsillectomy

Abstract: We herein describe an adult male patient who presented with tonsillitis, purpura, hematuria, and proteinuria. The serological analyses revealed elevated serum antistreptolysin, and the throat culture yielded Lancefield group A β-hemolytic streptococci. A renal biopsy revealed mild mesangial proliferation associated with granular mesangial depositions of IgA and C3, consistent with Henoch-Schönlein purpura nephritis (HSPN). Initially, the patient was treated with dipyridamole, which was followed by limited impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
(25 reference statements)
0
3
1
Order By: Relevance
“…However, these treatments had no effect on her native kidney. There are some reports from Japan that a tonsillectomy followed by steroid pulse therapy resulted in decreased proteinuria and improved renal function and pathological findings of HSPN in the native kidney or recurrent IgA nephropathy in a renal allograft . In this context, we believed our patient was refractory to the additional immunosuppressant and plasmapheresis and decided to perform a tonsillectomy followed by steroid pulse therapy.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…However, these treatments had no effect on her native kidney. There are some reports from Japan that a tonsillectomy followed by steroid pulse therapy resulted in decreased proteinuria and improved renal function and pathological findings of HSPN in the native kidney or recurrent IgA nephropathy in a renal allograft . In this context, we believed our patient was refractory to the additional immunosuppressant and plasmapheresis and decided to perform a tonsillectomy followed by steroid pulse therapy.…”
Section: Discussioncontrasting
confidence: 69%
“…Therapy for severe HSPN usually involves methylprednisolone pulse therapy with oral corticosteroids, immunosuppressive agents, antiplatelet drugs, and plasmapheresis. Tonsillectomy has also been used in some HSPN patients, with a marked improvement in renal function and proteinuria, but its benefit in the setting of recurrent disease in a renal allograft has not been reported. To our knowledge, this is the first report of the efficacy of tonsillectomy and steroid pulse therapy in a kidney transplant patient who developed active HSPN.…”
mentioning
confidence: 99%
“…Furthermore, Iwazu et al [15] reported that a monotherapeutic tonsillectomy was effective in inducing the clinical remission of HSPN. We have previously reported the effectiveness of tonsillectomy plus pulse therapy as a rescue therapy in an 11-year-old boy with HSP with recurrent purpura and persistent nephropathy [13].…”
Section: Discussionmentioning
confidence: 98%
“…As to the efficacy of tonsillectomy for HSPN, we reviewed 5 cases in which tonsillectomy was performed for HSPN including adults and children, and examined the epidemiology, clinical signs, treatment, and prognosis [12][13][14][15]. These published reports are listed in Table 1.…”
Section: Discussionmentioning
confidence: 99%